TEACHING LATVIAN AS A FOREIGN LANGUAGE IN THE MULTILINGUAL CLASSROOM: EXPERIENCE OF HUNGARY - Gaitniece, Lasma (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Multilingualism has been highly valued in the society from ancient times. Nowadays, along with the increase of people mobility and technology development, foreign languages competence and its acquisition learning becomes increasingly important. At the same time, minority language studies, taking into account a relatively small number of their users, provide the necessary contribution to the preservation and further development of the cultural heritage of the world nations. For example, the goal of the Department for Uralic Studies, Savaria Campus of the University of West Hungary, was to create a special unit and invite specialists in order to study and promote the Central European region, its culture, as well as the ancient Amber Route that stretched from the East coast of the Baltic Sea to the Adriatic coast and the Apennine Peninsula. From 1992 to 2013, this unit offered students an opportunity to learn Latvian as a foreign language, as well as the history of Latvia and its culture, Latvian literature, folklore and ethnogenesis. This article, based on the author's personal experience, is devoted to the specifics of learning and teaching of the Latvian language to Hungarian students, as well as translating the works of the Latvian authors into Hungarian.